(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
a comparative analysis of the petrographic and petrological and geochemical characteristics of the Early Carboniferous basalts of the areal (Beryozovskiy Suite Formation) and fissure (Grekhovka Suite) eruptions in the Magnitogorsk Megazone of the Southern Urals is carried out. Basalts are characterized by a porphitic texture with a pilotaxitic and intersertal bulk. Areal basalts are more ancient in age and differ from fissure basalts associated with the series of tension cracks, increased magnesia (Mg # = 46), alumina content (Al2O3> 16 wt.%) and potassium (K2O = 1.4 wt.%). Fissure basalts are characterized by high titanium(TiO2 = 2.7 wt.%) and iron content (FeOt = 13 wt.%). The trace element composition of these basalts is similar; they are characterized by increased concentrations of many incompatible elements, in particular, Ba, Th, U, Pb, but not Cs, Sr, Nb, and Ta. The analysis of petrological and geochemical diagrams showed that the studied rocks are derivatives of an enriched mantle source. A significant presence in the melt of terrigenous material with geochemical features of continental origin was revealed. It was shown that, when the melt was rising to the surface, probably, processes of assimilation of the island-arc frame and crystallization differentiation, more pronounced in basalts of the areal eruption, took place. It was established that the studied basalts underwent metasomatism of an uneven composition and intensity, which had a noticeable effect on the chemical composition of the studied rocks. For the selection of competent samples according to the grade of metasomatic alteration, 3 groups of samples were identified. It is concluded that, when working with highly altered rocks, the analyzes of Ca are not suitable for petrogenic reconstructions, and also the analyzes of Si, Mg and some large-ion lithophilic trace elements (Cs, Rb, Ba) are not always applicable.